Effect of ambulatory blood pressure monitoring guided antihypertensive treatment on renal progression in patients with chronic kidney disease: a randomized comparative study. Issue 2 (February 2021) - Kim, Yunmi; Kim, Jayoun; Lee, Sung Woo; Sung, Suah; Yoo, Tae-Hyun; Lee, Kyu-Beck; Hwang, Young-Hwan; Kim, Taehee; Kang, Sun Woo; Kim, Yeong Hoon; Oh, Kook-Hwan
Abstract : Objectives: Adequate blood pressure (BP) control is pivotal for managing chronic kidney disease (CKD). The optimal approach for monitoring BP to delay CKD progression is not yet clear. Methods: Patients with hypertension and CKD stage 3–4 were randomized into ambulatory blood pressure monitoring (ABPM) or office BP groups. All patients had ABPM at baseline and 18 months, and the ABPM group additionally underwent ABPM at 3 and 6 months. Each ABPM result was notified only for the ABPM group. The BP target was daytime ABP less than 135/85 mmHg for the ABPM group and office BP less than 140/90 mmHg for the office BP group. The primary outcome was decrease in estimated glomerular filtration rate (eGFR) during 18 months. Results: A total of 146 patients were randomized into the ABPM ( n  = 69) and office BP groups ( n  = 77). Although office BP was comparable in the two groups at baseline, daytime ABP was higher in the ABPM group (median 140 vs. 132 mmHg). Initial eGFR was 35.7 ± 12.5 ml/min per 1.73 m 2 in the ABPM group and 34.6 ± 12.0 ml/min per 1.73 m 2 in the office BP group. eGFR change was −5.5 [95% confidence interval (95% CI) −7.7 to  −3.4] ml/min per 1.73 m 2 in the ABPM group and −5.0 (95% CI −6.9 to −3.0) ml/min per 1.73 m 2 in the office BP group ( P  = 0.704). Renal events occurred in 10 patients (15.6%) from the ABPM group and five (7.1%) from the office BP group ( P  = 0.120). Conclusion: The present study did not show a beneficial effect of ABPM for controlling hypertension in CKD compared with conventional office BP monitoring in terms of renal outcomes. Abstract : Supplemental Digital Content is available in the text